2010
DOI: 10.1108/17542411011069882
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational barriers to women's career advancement in Lebanon

Abstract: PurposeThe purpose of this paper is to address the research gap on Lebanese female managers and to examine female managers' perceptions of their organizations in relation to women's career progression.Design/methodology/approachThe research was quantitative in nature. A survey questionnaire was used to collect data from 450 female managers. Measures included personal and demographic characteristics, organizational culture, organizational practices, organizational networks, mentoring and role modeling, tokenism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
144
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(154 citation statements)
references
References 84 publications
7
144
2
1
Order By: Relevance
“…Two of these studies are (Jamali, Sidani, & Safieddine, 2005), (Kattara, 2005), (Al-Lamky, 2007), and (Tlaiss & Kauser, 2010). While Jamali, et al, (2005) and Tlaiss and Kauser (2010) focused on constraints as perceived by Lebanese women managers in some occupation fields. Kattara (2005) focused on career challenges encountered by female managers in hotels in Egypt, whereas Al-Lamky (2007) examined challenges encountered by Arab women managers in Oman.…”
Section: Related Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of these studies are (Jamali, Sidani, & Safieddine, 2005), (Kattara, 2005), (Al-Lamky, 2007), and (Tlaiss & Kauser, 2010). While Jamali, et al, (2005) and Tlaiss and Kauser (2010) focused on constraints as perceived by Lebanese women managers in some occupation fields. Kattara (2005) focused on career challenges encountered by female managers in hotels in Egypt, whereas Al-Lamky (2007) examined challenges encountered by Arab women managers in Oman.…”
Section: Related Studiesmentioning
confidence: 99%
“…Yet, little attention has been given to how variables such as organizational culture, organizational networks and interpersonal relationships are related to challenges faced by women business leaders. Although Tlaiss and Kauser (2010) claimed that female managers in Arab countries encounter similar difficulties, it is very difficult to give generalizations due to cultural variables and differences in traditional norms in Arab countries. This literature review has confirmed that women managers in Arab countries encounter barriers that are associated with cultures that may hinder effective interaction, progression in careers, and networking.…”
Section: Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations